Eksplorasi Gender Gap pada Industri Teknologi Digital: Perspektif Pekerja Perempuan - Nur Isma Dewi; Pradytia Putri Pertiwi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The growth of the digital sector during the Coronavirus Disease (COVID) 19 pandemic has an impact on how individuals use technology and behave in social situations, introducing new work opportunities. However, work participation in the digital industry based on gender at the global level is still significant which can have an impact on gender gaps and the role of female workers. In terms of access to production and distribution of roles, female workers in the digital industry make widespread similarities with the presence of male workers. In-depth research is required to understand whether or not there is a gender gap in the digital industry, especially in the context of Indonesia, as a modern phenomenon. Previous studies have begun to discuss gender participation in non-digital industries, such as the garment sector, but have not yet discussed the dynamics of the gender gap and the role of women. This study utilizes social role theory to quantify the extent of the gender gap and the dynamics of women's roles in industrial technology. This study examines 3 female workers in 3 distinct digital technology companies using a qualitative method and a multiple case study approach. The results of this study reveals that the digital technology industry in the education, technology, and transportation sector is inclusive and promotes the role of women despite the fact that woman constitute a minority of workers. The role of women is supported by the equal of expectations towards the role of female workers, including the system of labor allocation and rewards that do not take gender into account. This research can further serve as a reference for other digital enterprise sectors and other industries when developing policies and programs to support and enhance the work role of women.